2017
DOI: 10.1093/cz/zox014
|View full text |Cite
|
Sign up to set email alerts
|

Like mother, like daughter: heritability of female Richardson’s ground squirrel Urocitellus richardsonii cortisol stress responses

Abstract: Activation of the hypothalamic–pituitary–adrenal (HPA) axis liberates glucocorticoids, which provides an acute indication of an individual’s response to stressors. The heritability of the stress response in wild mammals, however, remains poorly documented. We quantified the cortisol stress response of female Richardson’s ground squirrels (RGSs) to handling and physical restraint, testing for: (1) the effects of individual age, time of day, and sample latency; (2) repeatability within individuals; (3) narrow-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 88 publications
1
25
3
Order By: Relevance
“…High cortisol level was critically associated with weight loss in animal models showing depressive symptoms that were induced by repetitive corticosterone injections [ 9 , 10 ]. Consistent with those reports, we also confirmed the weight loss in Corti.Moms during pregnancy and postnatal Corti.Pups, suggesting that maternal cortisol level during pregnancy might influence the cortisol level in offspring ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High cortisol level was critically associated with weight loss in animal models showing depressive symptoms that were induced by repetitive corticosterone injections [ 9 , 10 ]. Consistent with those reports, we also confirmed the weight loss in Corti.Moms during pregnancy and postnatal Corti.Pups, suggesting that maternal cortisol level during pregnancy might influence the cortisol level in offspring ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More broadly, it is unclear whether individual differences in endocrine plasticity arise 211 from genetic, early-life, or environmental effects. Circulating glucocorticoids are shaped in part 212 by additive genetic effects [44][45][46][47], though the heritability of plasticity in glucocorticoids has not 213 been examined [18]. Early life exposure to fluctuating environments [48], maternal 214 glucocorticoids [49], and reduced parental care [50] all shape the glucocorticoid phenotype of 215 offspring [51][52][53], and could similarly shape variation in endocrine plasticity.…”
Section: Results 165mentioning
confidence: 99%
“…Furthermore, Bairos-Novak et al . [73] recently demonstrated that variation in the cortisol-based stress response of Richardson's ground squirrels is attributable more to heritability than environmental influences, suggesting that their physiological stress response may be more robust to external stressors than previously assumed. We attempted to collect faecal samples for glucocorticoid metabolite analysis from a variety of neighbours, though we observed that individuals vary in their ‘trapability'.…”
Section: Discussionmentioning
confidence: 99%